Corporate political activity of baby food companies in Thailand - Nisachol Cetthakrikul; Phillip Baker; Cathy Banwell; Matthew Kelly; Julie Smith (BMC, 2021)
Abstract Background Recent studies show corporate political activity (CPA) can have detrimental impacts on health policy processes. The Control of Marketing Promotion of Infant and Young Child Food Act B.E. 2560 (the Act) was implemented in Thailand in 2017, but there have been no studies documenting CPA during its policy processes. Furthermore, the effects of CPA on the Act and how non-industry stakeholders dealt with the CPA have not been explored. This study aimed to analyze the CPA of baby food companies in Thailand, its effects on the Act, and how policymakers have responded to CPA around the Act. Methods This qualitative study applied an established framework developed by Mialon and colleagues to collect and systematically analyze publicly available information from seven baby food companies with the highest percentage market share in Thailand. In-depth interviews were also used to explore how people involved in the policy process of the Act experienced the CPA of baby food companies, the consequent effects on the Act, and how they responded to the CPA. Results During development of the Act, baby food companies used two main strategies, 'information and messaging' and 'constituency building'. We found the companies met policymakers, and they employed evidence or provided information that was favorable to companies. Also, they established relationships with policymakers, health organizations, communities and media. The effects of CPA were that the scope of products controlled by the Act was reduced, and CPA led relevant people to misunderstand and have concerns about the Act. Officials and others countered the influence of CPA by raising awareness and building understanding among involved people, as well as avoiding contact with companies informally. Conclusions CPA consists of a variety of practices that resulted in a weakened Act in Thailand. Government officials and other non-industry stakeholders employed strategies to counteract this influence. This study suggests the Department of Health, and other relevant government agencies, would benefit from establishing safeguards and protections against CPA. Efforts to raise awareness about the harms of CPA within and outside of government and establish a systematic monitoring system, including avoid conflict of interest in policy process would improve policymaking and implementation of the Act.